2001
DOI: 10.1002/app.1559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glow‐discharge–treated cellulose acetate membrane surfaces for single‐layer enzyme electrode studies

Abstract: Cellulose acetate membranes (CA) were modified by means of plasma polymerization of ethylene diamine (EDA) and n-butylamine (n-BA). The motivation for this work was the application of a modified membrane for the single-layer enzyme electrode. A tubular reactor with the external radiofrequency (13.56 MHz) excitation was used. Surface modification was performed at 5, 10, and 15 W power (at 27 Pa working pressure) for 5, 10, 15 min. Modified surfaces were characterized in detail by FTIR-ATR, XPS (ESCA), contact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 19 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Each of these species alone can deactivate or disintegrate microorganisms, but they are more efficient in synergetic combinations (Fridman, 2008). The use of plasma is well established in areas such as surface modification for variable applications (Biederman et al, 2001;Mutlu et al, 1998), electrochemical sensors (Gunaydin et al, 2010), and preparation of functional surfaces e.g. amphoteric, bacterial anti-fouling (Akdogan and Mutlu, 2012;Cokeliler et al, 2007;Sen et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Each of these species alone can deactivate or disintegrate microorganisms, but they are more efficient in synergetic combinations (Fridman, 2008). The use of plasma is well established in areas such as surface modification for variable applications (Biederman et al, 2001;Mutlu et al, 1998), electrochemical sensors (Gunaydin et al, 2010), and preparation of functional surfaces e.g. amphoteric, bacterial anti-fouling (Akdogan and Mutlu, 2012;Cokeliler et al, 2007;Sen et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Besides an increase of hydrophilicity, pervaporation studies for separation of an isopropanol-aqueous mixture showed that these membranes have excellent selectivity for water. Other studies report on the surface modification of cellulose acetate membranes by plasma polymerization of amine monomers (24,25). The aim of these studies is to develop a glucose sensor for the food industry by immobilization of glucose oxidase onto the amino functionalized membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The improved wettability has been attributed to increasing amounts of polar groups (such as -NH 2 , -COO, -COOH, etc.) and surface oxidation (Liston et al 1993;Biederman et al 2001). PlzP with all monomers studied significantly reduced the water contact angle and increased wettability.…”
Section: Resultsmentioning
confidence: 97%
“…The density of amino groups per unit area was reported elsewhere (Mutlu et al 1991). Therefore, the presence of amino groups incorporated onto the PlzP-EDA surface (Mutlu et al 1999(Mutlu et al , 2008Biederman et al 2001;Saber et al 2002) form a steric barrier with very high density, repelling microorganisms approaching the surface, among the other precursors were studied in this research. The multi-component crosslinked EDA-based polymer coatings contributed to a significant reduction in adhesion of E. sakazakii when compared to bare 316 stainless steel.…”
Section: Resultsmentioning
confidence: 99%